Participatory Education and Co-management in Response to the Ecological Crisis: Insights from Humanities-Based Seminars on Ecological Issues - Masís Benavides, Gabriel (2025)
This article analyzes the contribution of participatory seminars in the Humanities at the University of Costa Rica to education on the ecological crisis from a humanistic, participatory, and interdisciplinary perspective. Through a qualitative methodology based on document analysis, pedagogical experiences, and critical reflection, it explores three main areas: the methodological evolution of the seminars, educational co-management as a democratic model, and the approach to ecological problems within general education. The theoretical framework draws on Paulo Freire’s critical pedagogy, participatory educational governance (UNESCO-IESALC), and education for sustainable development (UNESCO, 2020). The sources include institutional documents, academic studies, and student experiences. The research concludes that this educational model strengthens critical awareness, formative research, and social engagement, demonstrating that the articulation between the Humanities and ecology can foster meaningful learning and prepare professionals capable of addressing contemporary socio-environmental challenges.